Simultaneous virological and bacteriological screening of microbial isolates in Perna viridis / Ernie Suhaiza Radzi ... [et al.] - Radzi, Ernie Suhaiza; Mohamed, Emida; Rambely, Azlin Sham; Haron, Norhisham; Camalxaman, Siti Nazrina (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
The global consumption of shellfish has increased over the past few years concurrent with reports of viral and bacterial gastroenteritis outbreaks worldwide. This study was conducted to screen both viral and bacterial agents in Perna viridis using Transmission Electron Microscope (TEM) and molecular based detection methods. Direct genomic extraction methods were tested on mussels, which were purchased from Shah Alam wet market. Samples were subjected to Reverse Transcription-Polymerase Chain Reaction (RT-PCR) for viral screening and conventional PCR for bacterial detection. In this study, no viral agent was discovered but PCR amplification of the lamB gene yielded a single band at 309 bp, identifying E. coli as being present in Perna viridis tissues. Continuous monitoring of shellfish for pathogens will help ensure its safety for human consumption. Further studies focusing on the relationship and quantitative measurement of fecal indicator bacteria in coastal areas/aquaculture settings should be addressed.